The politics of language contact in the Himalaya - Sonntag, Selma; Turin, Mark; Open Book Publishers (Open Book Publishers, 2019)
"This highly original and timely collection brings together case studies from salient areas of the Himalayan region to explore the politics of language contact. Promoting a linguistically and historically grounded perspective, The Politics of Language Contact in the Himalaya offers nuanced insights into language and its relation to power in this geopolitically complex region. Edited by respected scholars in the field, the collection comprises five new research contributions by established and early-career researchers who have been significantly engaged in the Himalayan region. Grounded in a commitment to theoretically informed area studies, and covering Tibet (China), Assam (India), and Nepal, each case study is situated within contemporary debates in sociolinguistics, political science, and language policy and planning. Bridging disciplines and transcending nation-states, the volume offers a unique contribution to the study of language contact and its political implications. The Politics of Language Contact in the Himalaya is essential reading for researchers in the fields of language policy and planning, applied linguistics, and language and literary education. The detailed introduction and concluding commentary make the collection accessible to all social scientists concerned with questions of language, and the volume as a whole will be of interest to scholars in anthropology, sociolinguistics, political science and Asian studies."--Publisher's website.
Contributors -- Preface -- 0. Introduction: Language Politics and Language Contact / Selma K. Sonntag -- 1. Language Contact and the Politics of Recognition amongst Tibetans in the People's Republic of China: The rTa'u-Speaking 'Horpa' of Khams / Tunzhi (Sonam Lhundrop), Hiroyuki Suzuki, and Gerald Roche -- 2. What Happened to the Ahom Language? The Politics of Language Contact in Assam / Selma K. Sonntag -- 3. Transforming Language to Script: Constructing Linguistic Authority through Language Contact in Schools in Nepal / Uma Pradhan -- 4. The Significance of Place in Ethnolinguistic Vitality: Spatial Variations Across the Kaike-Speaking Diaspora of Nepal / Maya Daurio -- 5. Speaking Chone, Speaking 'Shallow': Dual Linguistic Hegemonies in China's Tibetan Frontier / Bendi Tso and Mark Turin -- 6. Concluding Thoughts on Language Shift and Linguistic Diversity in the Himalaya: The Case of Nepal / Mark Turin -- List of Tables and Figures -- Index.
Available through Open Book Publishers.
Includes bibliographical references and index.
Mode of access: World Wide Web.
Keywords: Language and culture -- Himalaya Mountains Region; Language and languages -- Political aspects -- Himalaya Mountains Region; Sino-Tibetan languages; Tibeto-Burman languages; Himalaya Mountains Region -- Languages